Transcriptome analysis and metabolic profiling reveal the key role of α-linolenic acid in dormancy regulation of European pear. (26th December 2018) - Gabay, Gilad; Faigenboim, Adi; Dahan, Yardena; Izhaki, Yacov; Itkin, Maxim; Malitsky, Sergey; Elkind, Yonatan; Flaishman, Moshe A
Abstract : New dormancy-associated regulatory genes and metabolites were identified in European pear bud, suggesting the key role of α-linolenic acid and DAM genes in dormancy phase transition. Abstract: Deciduous trees require sufficient chilling during winter dormancy to grow. To decipher the dormancy-regulating mechanism, we carried out RNA sequencing (RNA-Seq) analysis and metabolic profiling of European pear ( Pyrus communis L.) vegetative buds during the dormancy phases. Samples were collected from two cultivars that differed greatly in their chilling requirements: 'Spadona' (SPD), a low chilling requirement cultivar; and Harrow Sweet (HS), a high chilling requirement cultivar. Comparative transcriptome analysis revealed >8500 differentially expressed transcripts; most were related to metabolic pathways. Out of 174 metabolites, 44 displayed differential levels in both cultivars, 38 were significantly changed only in SPD, and 15 only in HS. Phospholipids were mostly accumulated at the beginning of dormancy, sugars between before dormancy and mid-dormancy, and fatty acids, including α-linolenic acid, at dormancy break. Differentially expressed genes underlying previously identified major quantitative trait loci (QTLs) in linkage group 8 included genes related to the α-linolenic acid pathway, 12-oxophytodienoate reductase 2-like, and the DORMANCY-ASSOCIATED MADS-BOX ( DAM ) genes, PcDAM1 and PcDAM2, putative orthologs of PpDAM1 and PpDAM2, confirming their role for the first time in European pear. Additional new putative dormancy-related uncharacterized genes and genes related to metabolic pathways are suggested. These results suggest the crucial role of α-linolenic acid and DAM genes in pear bud dormancy phase transitions.